On income tax avoidance: the case of Germany - Oliver Lang; Karl-Heinz Nöhrbaß; Konrad O. Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
In this paper, we present a micro estimate determining taxable income as a function of gross income and all major deduction options depending on household and asset categories. It is shown that tax savings strongly increase with increasing income, resulting in a decreasing effective marginal tax rate for the highest income groups. We compute a lower bound on 1983 aggregate income tax losses to the German fiscal authorities of DM 72b, or of 45 % of wage and income taxes paid in 1983. The estimate of tax loss exceeds estimates for other countries by orders of magnitude.
Keywords: 330